DESIGN OF CIRCULATION HOSPITAL SERVICE IN THE NEW NORMAL ERA - Randy Pratama Salisnanda (Jurnal IPTEK, 2023)
Health care buildings are experiencing extreme challenges due to the COVID-19 pandemic worldwide, the high global death rate due to the pandemic has forced hospitals to make changes and improve health service strategies to minimize the impact of transmission and hospital readiness in dealing with other infectious diseases. The design of this service circulation design is expected to be able to improve the quality of service to the community and users related to the ideal, thorough, thorough, fast, precise and correct service excellence principles. Using analytical methods, data sources were obtained through studies on hospital building planning with a separate circulation system, government regulations related to infectious diseases, and the shortcomings of the previous hospital building circulation system, the conclusion resulted in a building circulation design planning that has 3 zoning (red, yellow, red zones). and green) by providing differentiation in circulation related to the function of each room, the classification of visitors and the flow of patients in and out, to improve hospital services and safety against unpredictable conditions in the future such as the current pandemic era.